KEDUDUKAN HARTA WARISAN DENGAN KETIADAAN AHLI WARIS DALAM HUKUM ADAT DAYAK KANAYATN - NIM. A1012221006, BONIFASIA LIGUSTINI (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Conceptually, inheritance in customary law is the transfer of inherited property from heir to heir. However, the absence of heirs leaves inherited assets in a situation without an